Transformation of Indian automobile industry through inter-organization IT initiative : AutoDX (B) - Verma, Sanjay (London : Indian Institute of Management, Ahmedabad, 2018)
The case centres on the 2015 common data exchange, an initiative for all automobile manufactures in India to share data. Part B in the two part cases series goes through the three phases of implementing the common data exchange initiative: standardization of data, application development and implementation and marketing and systems integration. Finally the cases discusses problems encountered during implementation.
Originally Published InVerma, S. (2018). Transformation of Indian Automobile Industry Through Inter-Organization IT Initiative: AutoDX (B). IIMA/IS0135(B). Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Electronic data interchange -- India -- Case studies; Automobile industry and trade -- India -- Case studies